No age effect in the prevalence and clinical significance of ultra-high risk symptoms and criteria for psychosis in 22q11 deletion syndrome: Confirmation of the genetically driven risk for psychosis? - Armando, Marco (PLoS One, 2017)
BACKGROUND: The 22q11.2 deletion syndrome (22q11DS) is one of the highest known risk factors for schizophrenia. Thus, the detection of 22q11DS patients at particularly high risk of psychosis is important, yet studies on the clinical significance of the widely used ultra-high risk (UHR) criteria in 22q11DS are inconclusive. Since age was reported to moderate clinical significance of UHR symptoms in community samples, we explored whether age at presentation of UHR symptoms and criteria may explain part of this heterogeneity. METHODS: 111 patients with 22q11DS (8–30 years; 15.7±4.7) were assessed for UHR symptoms/criteria. Information on diagnoses, psychosocial functioning, and IQ were collected. RESULTS: Any UHR symptom was reported by 38.7%, any UHR criterion by 27%. No significant influence of age on the prevalence of UHR symptoms or criteria was detected. Moreover, age did not significantly modulate the association between UHR symptoms and functioning. However, significant interaction terms suggested that younger age groups were more likely to meet UHR criteria in the presence of UHR symptoms compared to the adult group. DISCUSSION: Compared to the general population, prevalence of UHR symptoms and criteria was 3.8-fold and 20.8-fold in our 22q11DS sample. Contrary to the general population, age only modulated the prevalence of UHR criteria among those with UHR symptoms, but not their prevalence per se or their clinical significance. This suggests that UHR symptoms might develop as a trait factor in terms of a genetically driven schizotypal disposition in 22q11DS, thus necessitating future studies on psychosis-risk indicators in this genetic high-risk group.